Perencanaan Operasional melalui Keputusan Strategis yang Terukur : Mewujudkan Proyeksi Masa Depan Organisasi Pendidikan Islam - Mia Nurussafaah; Nisfani Alfi Fahrezi; Rendi Saputra; Mardiyah Mardiyah; Sukma Ayu Raganingtyas; Shelvi Chairunnisak (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Strategic decision-making ability is an important skill that must be possessed by the leaders of Islamic educational institutions to support the achievement of educational goals, improve the quality of learning, and build institutional governance in accordance with Islamic values. The purpose of this study is for operational planning in Islamic educational organizations through measurable strategic decision-making. The focus of the study is directed at how operational definitions of programs, indicators, activities, and scheduling based on the academic calendar can reflect the readiness of educational institutions in facing future challenges. This study uses a library research method by collecting data from various written sources such as books, scientific journals, and relevant official documents. The results of the study show that clarity in formulating program indicators, selecting relevant persons in charge, and integration be-tween strategy and operational activities can increase the effectiveness of achieving the vision and mis-sion of Islamic educational institutions. Therefore, operational planning is not only technical, but is an integral part of the strategic management of Islamic education.